Precursor B-lineage acute lymphoblastic leukemia patients with aberrant natural killer cell and T cell – lineage antigen expression: experience from a tertiary cancer care center - Karthik Bommannan; Jhansi Rani Arumugam; Venkatraman Radhakrishnan; Jayachandran Perumal Kalaiyarasi; Nikita Mehra; Tenali Gnana Sagar; Shirley Sundersingh (Hematology, Transfusion and Cell Therapy, 2022)
Introduction: Flow cytometric immunophenotyping (FCI) plays a major role in diagnosing hematologic malignancies. In patients diagnosed with precursor B-lineage acute lymphoblastic leukemia (B-ALL), expression of certain non-lineage/cross lineage antigens is of prognostic and cytogenetic relevance. There is a paucity of studies that have comprehensively analyzed the clinical and laboratory profiles of B-ALL patients showing aberrant T/natural killer (NK) cell antigen expression. Materials and methods: This is a prospective study where 152 consecutive B-ALL patients were analyzed for aberrant expression of T/NK cell antigens (CD1a, CD5, CD4, CD7, CD8 and CD56) by FCI. The clinical and laboratory profile of these T/NK-cell antigen-expressing B-ALL patients was statistically analyzed against conventional B-ALL patients. Results: In our B-ALL cohort, CD5, CD7 and CD56 expression were observed in one, six and nine patients, respectively. CD56-expressing B-ALL patients were predominantly children (89%) and presented as standard clinical risk (p = 0.010) disease with frequent ETV6-RUNX1 fusion (p = 0.021) positivity. On the contrary, CD7-expressing B-ALL patients were adolescent-young adult/adult-age skewed (83%) and had an adverse cytogenetic profile (p = 0.001), especially for the frequent presence of BCR-ABL1 fusion (p = 0.004) and KMT2A rearrangement (p = 0.045). CD7-expressing B-ALL patients had inferior event-free survival (p = 0.040) than their CD56-expressing counterparts, but there was no significant difference in the overall survival (p = 0.317). Conclusion: In comparison to conventional B-ALL patients, there are significant differences in the age, cytogenetic profile and event-free survival of T/NK-cell antigen-expressing B-ALL patients.